(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Since ancient times, India has been renowned throughout the world for its ayurvedic therapies. Itraconazole and fluconazole have been widely used as preventative measures and therapeutic agents for systemic fungal infections. These antifungal drugs have negative side effects and moreover numerous pathogenic microorganisms are continuously acquiring resistance to them. Therefore, there is resurgence to search for more effective and less toxic novel antifungal agents from plant sources. Hence, in the current study we aimed for phytochemical screening and determination of antifungal activities of leaf extract of Emblica officinalis (Amla). Leaves of E. officinalis was subjected to successive solvent extraction by continuous hot extraction (Soxhlet) with double distilled water. Results delineated the major phytochemical present in the aqueous (Aq.) extract of leaves of E. officinalis were alkaloids, flavonoids, proteins & amino acids, saponins, phenolic compounds, tannins, carbohydrates, reducing sugars. Moreover, quantitative estimation of phytochemicals in Aq. extract of leaves of E. officinalis revealed that total polyphenol quantity was found to be highest (24.43 GAE) when compared with total flavonoid quantities (6.83 GAE). Furthermore, Aq. extract of leaves of E. officinalis (Amla) possess potential antifungal activity against Aspergillus niger, Aspergillus fumigates, Candida tropicalis and Penicillium crysogenum. In conclusion, this study results delineated that leaves of E. officinalis (Amla) could be used in herbal medicine for treatment of fungal diseases.